RETRACTED - Temporary ditches are effective in reducing soil erosion in hilly areas. An evaluation with the RUSLE model - Francaviglia, Rosa; Neri, Ulderico (Italian Journal of Agronomy, 2020)
This paper has been retracted. See the Retraction note at: https://doi.org/10.4081/ija.2021.1960